2016
DOI: 10.1176/appi.ajp.2015.15020162
|View full text |Cite
|
Sign up to set email alerts
|

Depression-Related Increases and Decreases in Appetite: Dissociable Patterns of Aberrant Activity in Reward and Interoceptive Neurocircuitry

Abstract: Objective Appetite and weight changes are common but variable diagnostic markers in major depressive disorder: some depressed individuals manifest increased appetite, while others lose their appetite. Many of the brain regions implicated in appetitive responses to food have also been implicated in depression. It is thus remarkable that there exists no published research comparing the neural responses to food stimuli of depressed patients with increased versus decreased appetites. Method Using functional magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
121
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(149 citation statements)
references
References 48 publications
11
121
2
3
Order By: Relevance
“…The necessity of this pathway for intact drugseeking behavior is supported by translational research in rodents, where temporary inactivation of the interoceptive insula disrupts drug-induced place preference (Contreras et al, 2007) and drug self-administration (Forget et al, 2010), and by clinical research in human patients identifying that insula lesions disrupt addiction (Naqvi et al, 2007). Similarly, in psychiatric disorders such as anorexia and major depression, abnormal interoceptive insula activity is associated with abnormal feeding behavior (Avery et al, 2014;Kerr et al, 2016;Simmons et al, 2016). Taken together, the identification of this relationship between craving and interoceptive activity in the insula may serve to identify specific neural targets for interventions to help humans discontinue unhealthy, but rewarding, behaviors (see Supplementary Materials for limitations and additional discussion).…”
Section: Discussionmentioning
confidence: 99%
“…The necessity of this pathway for intact drugseeking behavior is supported by translational research in rodents, where temporary inactivation of the interoceptive insula disrupts drug-induced place preference (Contreras et al, 2007) and drug self-administration (Forget et al, 2010), and by clinical research in human patients identifying that insula lesions disrupt addiction (Naqvi et al, 2007). Similarly, in psychiatric disorders such as anorexia and major depression, abnormal interoceptive insula activity is associated with abnormal feeding behavior (Avery et al, 2014;Kerr et al, 2016;Simmons et al, 2016). Taken together, the identification of this relationship between craving and interoceptive activity in the insula may serve to identify specific neural targets for interventions to help humans discontinue unhealthy, but rewarding, behaviors (see Supplementary Materials for limitations and additional discussion).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the converse may also be true. Simmons and colleagues observed that obese adults experiencing increased appetite during a major depressive episode rated food cues as more hedonically pleasing and exhibited greater activity in reward neurocircuitry in response to food cues [50]. Critically, however, it was the activity of the dorsal mid insula (bilaterally), and not the brain’s reward circuitry, that was correlated with the subjects’ hedonic ratings for foods.…”
Section: Interoceptive Hypersensitivity May Predispose Some Individuamentioning
confidence: 99%
“…Penelitian ini menjadi salah satu pendukung dari artikel yang ditulis oleh Simmons et al (2015) dengan subjeknya adalah wanita 10 . Hasil dari Simmons et al (2015) menjelaskan bahwa depresi pada seseorang memang mempunyai dua pengaruh terhadap nafsu makan seseorang 10 . Beberapa orang dengan depresi tinggi bisa meningkatkan nafsu makan bahkan bisa menurunkan nafsu makan.…”
Section: Metodeunclassified
“…Beberapa orang dengan depresi tinggi bisa meningkatkan nafsu makan bahkan bisa menurunkan nafsu makan. Hasil akhir dari keduanya akan terlihat bagaimana seseorang itu menyisakan makanan 10 . Pada kondisi depresi, stimulan tekanan hemodinamik otak pada seseorang memiliki hipoaktifasi yang mempengaruhi fisiologis tubuh.…”
Section: Metodeunclassified
See 1 more Smart Citation